2020
DOI: 10.1183/20734735.0161-2020
|View full text |Cite
|
Sign up to set email alerts
|

Improving continuity of care of patients with respiratory disease at hospital discharge

Abstract: Continuity of care refers to the delivery of coherent, logical and timely care to an individual. It is threatened during the transition of care at hospital discharge, which can contribute to worse patient outcomes. In a traditional acute care model, the roles of hospital and community healthcare providers do not overlap and this can be a barrier to continuity of care at hospital discharge. Furthermore, the transition from inpatient to outpatient care is associated with a transition from acute to chronic diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Radical prostatectomy is the most effective and commonly used treatment for prostate cancer, but patients usually have serious psychological problems after surgery, and the body is traumatized, and the patient's postoperative immune status is poor [12][13][14][15]. Patients still need professional health guidance after they are discharged.…”
Section: Discussionmentioning
confidence: 99%
“…Radical prostatectomy is the most effective and commonly used treatment for prostate cancer, but patients usually have serious psychological problems after surgery, and the body is traumatized, and the patient's postoperative immune status is poor [12][13][14][15]. Patients still need professional health guidance after they are discharged.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the inaccuracy seen in AECOPD discharge notes and the lack of information continuity required in the transition of care result in worse patient outcomes, including a high re-admission rate. 45 In this regard, various improvement measures have been proposed. For example, Epstein et al designed and successfully implemented a decision support tool to automatically generate discharge recommendations based on GOLD guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory conditions are a key contributor to acute admissions, accounting for 850,000 pre-pandemic emergency hospital visits per year, with a yearly cost to the NHS of £9.9 billion 35 . Continuity of care is also important in this often multimorbid group, with integrated respiratory services providing holistic care for patients between the primary and secondary care interface shown to improve patient outcomes 36 , 37 . The National Institute for Health and Care Excellence (NICE) recommends multidisciplinary hospital-at-home schemes for managing selected patients with exacerbations of COPD 38 and this study has shown that the NHS GGC CRRT was able to effectively provide this service resulting in a reduction in emergency department attendances for COPD across the Trust, low rates of admission and death amongst CRRT patients, and no nosocomial COVID-19 infections.…”
Section: Discussionmentioning
confidence: 99%